Two‐Dimensional Materials Applied in Membranes of Redox Flow Battery. Issue 3 (5th January 2023) - He, Murong; Guan, Minyuan; Zhan, Ruifeng; Zhou, Kaiyun; Fu, Hu; Wang, Xinan; Zhong, Fangfang; Ding, Mei; Jia, Chuankun
Abstract: Redox flow batteries (RFBs) are one of the most promising techniques to store and convert green and renewable energy, benefiting from their advantages of high safety, flexible design and long lifespan. Membranes with fast and selective ions transport are required for the advances of RFBs. Remarkably, two‐dimensional (2D) materials with high mechanical and chemical stability, strict size exclusion and abundantly modifiable functional groups, have attracted extensive attentions in the applications of energy fields. Herein, the improvements and perspectives of 2D materials working for ionic transportation and sieving in RFBs membranes are presented. The characteristics of various materials and their advantages and disadvantages in the applications of RFBs membranes particularly are focused. This review is expected to provide a guidance for the design of membranes based on 2D materials for RFBs. Abstract : Membranes with high ion‐selectivity are desirable for the improvements of redox flow batteries (RFBs). Remarkably, two‐dimensional (2D) materials with good stability, strict size‐exclusion effects and abundant functional groups, have attracted attentions in the energy fields. This review focuses on the characteristics of 2D materials and their applications in RFBs membranes. Finally, some advices are provided for the future design of 2D materials for advanced RFBs membranes.